Tradition or revolution? The difficult "turning point" in Italian Children’s Literature - Anna Antoniazzi (Strenae)
The 1960s and 1970s in Italy was a complex period, full of often contrasting stimuli from different directions. The imaginary worlds of children participated in what was happening at a social and cultural level, albeit in a more muted way. By analysing sources from the publishing world, TV programmes for children and other mass media, it is possible to identify a profound ambiguity and ambivalence in the material proposed. On the one hand there was an abundance of writers, artists and thinkers ready to place childhood at the very centre of educational processes, attributing to it a heretofore unthinkable autonomy and dignity. On the other, it is possible to sense in many narrators a firm retreat into tradition, conservatism and the maintenance of a status quo based on stories of “fine sentiments”, filial love and containment of emotions…Even though there was much distance between these contradictory visions, their incongruity was able to spark new curiosities in (perhaps not only) children, to suggest new existential questions and open up new interpretive perspectives.